OPTIMALISASI PEMASARAN UNTUK MENDUKUNG DAYA TARIK WISATAWAN DI DESA TAJEN MELALUI ENTRANCE TICKET - Wulandari, Made Pradnya; Sukadana, I Wayan (FKIP Universitas Wisnuwardhana, 2023)
Tourism industry, one of the most effective instrument for promoting regional development, community empowerment, and efforts to reduce poverty. This study aims to solve tourism-related problems in Tajen Village, Penebel District, Tabanan which has great potential in terms of agriculture and culture. The scope meaning of entrance tickets, the advantages and benefits of making entrance tickets, the design of entrance tickets, and the ongoing plans for this entry ticket in Tajen Village. The method used is direct observation, discussions with Ajik Kisuda and designing entrance tickets. The results of this entry ticket design are expected to realize the Pokdarwis program in increasing community participation in the management and implementation of operational activities for the implementation of the Tajen Tourism Village offered to tourists. The entrance design used as a work program later if it continues to carry out it will bring better benefits to tajen village. To bring about sustainable empowerment of people, in accordance with the desired vision from tajen village to become a tourist village. So that with this entry ticket it can attract tourists to visit as well as a symbolic form of the Tajen Tourism Village.